Prognostic implications of admission hyperglycemia for inhospital morbidity and mortality in acute coronary syndrome - Oraha, Ameer A.; AL Ruba'ae, Salim M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Diabetes mellitus is a well known risk factor for acute coronary syndrome but the hypothesis that patients with acute phase hyperglycemia, regardless the previous diagnosis of diabetes, have worse prognosis than those with normal glucose values is controversial. This paper aims to estimate the prevalence of admission hyperglycemia, its effect on in-hospital prognosis of diabetic and non-diabetic patients with acute coronary syndrome, and to compare it with 2nd day fasting plasma glucose as a prognostic marker.Methods: One hundred patients, (59) diabetic and (41) non-diabetic, with documented acute coronary syndrome enrolled in this study over the period of June/ 2009-Jan./2010 from coronary care unit of Baghdad Teaching Hospital, who were thoroughly examined, hyperglycemia documented on admission and next day, then followed up daily during hospitalization for development of complications or death.Results: Heart failure and recurrent cardiac ischemic events were significantly more common in diabetic than non-diabetic patients (P-value:0.04 for both),while arrhythmias, cardiogenic shock and mortality rate were not significantly different between both study groups. Admission hyperglycemia more than 200mg/dl was associated with higher incidence of cardiogenicshock, recurrent ischemic events, heart failure, and death in non-diabetic patients (P-value 0.009, 0.022, 0.025, 0.026 respectively) but no more arrhythmias, and in diabetic patients admission hyperglycemia was only associated with more recurrent ischemic events (P-value 0.017). Second day fasting plasma glucose more than 126mg/dl was associated with higher incidence of heart failure in non-diabetic patients and more recurrent ischemic events in both study groups.Conclusion: Admission hyperglycemia is a poor in-hospital prognostic marker in non-diabetic & to lesser extend in diabetic patients suffering acute coronary syndrome.